2003
DOI: 10.1210/en.2002-221001
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Evidence of Organic Ion Transporters in the Rat Adrenal Cortex with Adrenocorticotropin-Regulated Zonal Expression

Abstract: Experimental evidence suggested that secretion of steroid hormones from adrenocortical cells involves carrier-mediated transport: Cortisol release from, and uptake of p-[3H]aminohippurate into, bovine adrenocortical cells showed properties of the renal p-[3H]aminohippurate/anion exchanger OAT1. Other poly-specific transporters such as organic anion-transporting polypeptides (oatps) and organic cation transporters (OCTs) could also be involved in steroid hormone release. A homology-cloning procedure was establi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…In 2003, rOat1 mRNA was detected in the outer zona fasciculata of the rat adrenal gland [133]. Furthermore, adrenocorticotropic hormone (ACTH) administration to rats increased rOat1 mRNA in the adrenal gland [133] and, consistent with this finding, hypophysectomy reduced adrenal gland rOat1 mRNA expression [133].…”
Section: Glucocorticoidsmentioning
confidence: 64%
See 1 more Smart Citation
“…In 2003, rOat1 mRNA was detected in the outer zona fasciculata of the rat adrenal gland [133]. Furthermore, adrenocorticotropic hormone (ACTH) administration to rats increased rOat1 mRNA in the adrenal gland [133] and, consistent with this finding, hypophysectomy reduced adrenal gland rOat1 mRNA expression [133].…”
Section: Glucocorticoidsmentioning
confidence: 64%
“…These observations raised the question as to whether rOat1 is involved in the transport of corticosteroids out of the adrenal cortex. In support of this hypothesis, corticosterone was demonstrated to inhibit rOat1-mediated PAH uptake into expressing X. laevis oocytes [133]. These findings indicated that ACTHtriggered secretion of glucocorticoids from the adrenal cortex may depend on rOat1, which is possibly upregulated to facilitate the exit of glucocorticoids, however, rOat3 has not been assessed.…”
Section: Glucocorticoidsmentioning
confidence: 95%
“…The release would not be rapidly controlled in such a mechanism and would continue constitutively. Recent in vitro studies (30) have demonstrated the intracellular retention of steroids against a concentration gradient at the plasma membrane. The last few years have witnessed the description of a steroid transport mechanism involving organic anion transport.…”
Section: Resultsmentioning
confidence: 99%
“…In situ hybridizations and immunohistochemical analyses localized rat OAT1 to the zona fasciculata of the rat adrenal cortex, where cortisol synthesis and release take place. Importantly, OAT1 mRNA expression was strongly increased by treatment of rats with ACTH in vivo (2). Recently, we (1) reported a transporter protein-mediated translocation of cortisol in human (h)OAT3-expressing oocytes, and we also demonstrated probenecid-, cimetidine-, and glutarateinhibitable estrone sulfate (ES) uptake by forskolin-treated human adrenocortical cells (NCI-H295R).…”
mentioning
confidence: 88%